Subgaleal coiling of the proximal and distal components of a ventriculoperitoneal shunt - Kloss, Brian T (Springer, 2012)
Migration is a rare complication of venticuloperitoneal shunts and is thought to be associated with the "memory" of the plastic tubing and the windlass effect of neck flexion and extension. The purpose of this case report is to detail a very rare case of complete distal to proximal shunt migration.